Evaluacion y difusion de estrategias para el manejo integrado de plagas de frijol - Rivadeneira, C.; Prada, P.; Córdova, P.; Ramon, M.T.; Soto P., O. (International Center for Tropical Agriculture, 1991)
Information is given of an integrated bean pest management subproject in Ecuador, Peru, Colombia, and Bolivia as to responsible institutions and technicians, duration, background, justification, objectives, methodology, activity chronogram, description of activities, results expected, and budget. (CIAT)